Evaluation of Drainage Channel Capacity in Griya Rumbai Lestari Complex, Limbungan Baru Village with EPA SWMM 5.2 : Evaluasi Kapasitas Saluran Drainase di Jalan Harapan Kelurahan Limbungan Baru dengan Perangkat EPA SWMM 5.2 - Vauzhea Sherlina; Bismi Annisa (Jurnal Teknik Sipil dan Lingkungan, 2022)
The high level of land use to meet the population's needs for land for settlement has led to an increase in land cover which results in high rates of rainwater runoff and reduces the amount of water that experiences infiltration. The study was conducted to review the ability of existing drainage channels to accommodate rainwater runoff and provide technical solutions to overflowing canals. The main components used in planning are rainfall to calculate the design discharge, as well as dimensions of existing drainage, soil infiltration rate test, catchment area, percentage of impermeable area, and soil elevation as the main input data in the drainage capacity simulation using the EPA SWMM 5 tool. 2 and results that the drainage is able to accommodate rainwater runoff. However, the simulation also shows that there are flood points due to higher outfall elevations so that the existing drainage is not able to drain rainwater runoff optimally. Based on this, a rainwater harvesting system (PAH) and infiltration wells are planned as an effort to manage and utilize rainwater runoff by collecting and reabsorbing rainwater runoff into the ground.